2(m+14)=-10

Simple and best practice solution for 2(m+14)=-10 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(m+14)=-10 equation:


Simplifying
2(m + 14) = -10

Reorder the terms:
2(14 + m) = -10
(14 * 2 + m * 2) = -10
(28 + 2m) = -10

Solving
28 + 2m = -10

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-28' to each side of the equation.
28 + -28 + 2m = -10 + -28

Combine like terms: 28 + -28 = 0
0 + 2m = -10 + -28
2m = -10 + -28

Combine like terms: -10 + -28 = -38
2m = -38

Divide each side by '2'.
m = -19

Simplifying
m = -19

See similar equations:

| -19=-2(g-12)+-19 | | -19a+11a+19a-13a-3=-9 | | -46b-5=3b+9 | | 3h-h-12h+12=2 | | -16x+176=19x+1 | | 14x+9=7x+31 | | -3(x-7)+9x=6x+11 | | 4(6-y)+10=-10(y-2)-9 | | 3v+v-3v=9 | | 5=7-9 | | 8.425-3.143x=9.214x+12.081 | | a+7=-14 | | -42x-12=-6(6x-4) | | -13=12+m | | c=3+-3 | | -1+n=-20 | | -11x+10=-12x+8 | | 9x+3y+1y-0.9x= | | 10y-17=6y-12 | | -6x-10=38 | | 9x^2+18x-39=0 | | -10=h-6 | | -9+13x=11-x | | 5.39x+16=29.0521+4x | | 11-5x+3=2x+4-3x | | -13m+14-11=7(-m+13)+2 | | 15x+2=9x+22 | | 7(7y+17)=16+8(5y+5) | | 4x^5-22x^3-80x=0 | | -6p+7=-5(2p+13) | | 10(2)-3x=15 | | -16w=8(-w+6) |

Equations solver categories